â€œMOPHETHâ€ - TINDAKAN PROFETIS MAKNA SIMBOLIS Dan Relevansinya Bagi Gereja Masa Kini - Gunawan, Yehuda Indra; Pakiding, Herman (Shift Key : Jurnal Teologi dan Pelayanan, 2020)
Symbolic prophetic action is one method of delivering God's message to His people by means of the prophet. It can be used as a social and theological criticism, which brings a good change in Israelitesâ€™ life. Hoped that this research can answer the question which is relevant to the symbolic prophetic action carried out by the Old Testament prophets for the church today. Socio-religious questions used to describe classical to modern social theories. The "trinity of sociology" form the basis in taking action to prevent symbolic prophetic actions. The results show that some of the symbolic prophetic actions that quote the word "mopheth" are the prophets themselves who become "omens" coming to God's judgment on Israel for rebellion to visit God.